Evaluation of MBKM Curriculum Management in Encouraging Links and Matches with the Industrial World - Mudhofar, Mudhofar; Fathorrahman, Fathorrahman; Sumarsih, Sumarsih; Christianto, Theodorus Erick; Hardian, Dafyar Eliadi (Journal of English Language and Education, 2025)
The Independent Learning-Independent Campus (MBKM) program is a breakthrough policy of the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek) to increase the relevance of higher education to the needs of the workforce. This study aims to evaluate the MBKM curriculum management in promoting linkages and matches between universities and industry. Using a descriptive qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis with various stakeholders. The results show that MBKM has succeeded in building university-industry collaboration through internships, collaborative projects, and work-based learning, which have contributed to improving students' technical competencies and soft skills. However, key challenges include: (1) the gap between the orientation of long-term competency development of universities and the short-term needs of industry, particularly in the technology and digital fields; (2) administrative complexity in recognizing credits and synchronizing schedules; and (3) evaluation mechanisms that are still administrative in nature and do not adequately measure the long-term impact on graduate employability. This study recommends strengthening strategic partnerships, simplifying administrative procedures, and developing an outcome-based evaluation system and structured feedback mechanisms to optimize the MBKM program going forward.